STRATEGY FOR THE DEVELOPMENT OF GLOBAL MARKETING OF SERVICES - KHURDEI, VIKTORIIA; DATSENKO, VIKTORIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Globalization and the strengthening of the international conference require new approaches to the development of marketing services. The growth of the global services economy, as well as the growth in the volume of exports of services by Ukraine to the international market, confirms the need to develop a strategy for the development of global marketing of services, which determines the relevance of the research topic. The latest publications of Ukrainian and foreign scientists (such as S.E. Sardak, S.V. Kovalchuk, O.M. Kovinko, I.V. Lisovsky, L.O. Ivanova, B.B. Semak, Treityak M.V., T.M. Tsigankova, Brinker S., Enerson M., Mason R., Corbishley K.) are analyzed, who in their works highlight the main factors that affect the formation of the main trends and the development of global marketing of services. It has been found that global marketing of services is a philosophy, strategy and tactics of business, which is based on a comprehensive analysis and segmentation of the international market of services, the development of an optimal marketing complex (7P) aimed at meeting consumer expectations and harmonious balancing of the company’s interests in order to promote and implement services in the international market. The trends of global marketing of services are revealed: new technologies, digital environment, processes of deglobalization, innovations and marketing without marketing. The elements of the strategy for the development of global marketing of services are characterized: product, price, place, new markets, content, social networks, ways of interaction, digital technologies, professionalism of employees, automation of services, marketing budget, optimization of marketing strategy management, their features and possible measures for adapting the strategy for the development of global marketing of services in companies.